Airway organoids as models of human disease. (29th April 2020) - van der Vaart, J.; Clevers, H.
Abstract: Studies developing and applying organoid technology have greatly increased in volume and visibility over the past decade. Organoids are three‐dimensional structures that are established from pluripotent stem cells (PSCs) or adult tissue stem cells (ASCs). They consist of organ‐specific cell types that self‐organize through cell sorting and spatially restricted lineage commitment to generate architectural and functional characteristics of the tissue of interest. The field of respiratory development and disease has been particularly productive in this regard. Starting from human cells (PSCs or ASCs), models of the two segments of the lung, the airways and the alveoli, can be built. Such organoids allow the study of development, physiology and disease and thus bridge the gap between animal models and clinical studies. This review discusses current developments in the pulmonary organoid field, highlighting the potential and limitations of current models. Abstract : Content List ‐ 16th Key symposium: "The origin of cancer"